IMPLEMENTATION OF THE CASH SYSTEM IN THE INFORMATION SYSTEM OF CASH RECEIVING AND DISTRIBUTIONS - Diana, Wahyu; Munandar, Agus (Jurnal Ecoment Global, 2022)
In the current era of technological advances, the use of computer accounting systems has become a major part that must be applied in a company to avoid errors and improve performance effectiveness. Several companies that have implemented the use of the system are the hotel sector. The purpose of this study is the system application used can be used to support cash receipts and disbursements to produce a financial report that meets the standards. The method used in this research is descriptive with a qualitative approach which is supported by collecting information on previous research that has been carried out. Based on the results of the analysis of research conducted in the hospitality industry, the system has been used as a standard for recording financial statements to minimize errors. The system used already has its own parts which are quite easy for the user and more practical to make an income statement. From this study found differences between previous studies, namely the differences between the systems used by manufacturing and hotel companies. But overall, the focus of each of these systems has the same goal, namely, to produce financial reports.